Pengaruh Perbandingan Kecambah Kacang Merah dengan Kacang Merah Terhadap Karakteristik Fisikokimia dan Sensoris Susu Nabati - Naomi, Risanti; Wisaniyasa, Ni Wayan; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p07, 2024)
Kidney bean sprouts have a higher nutritional value than red beans; however, when used as vegetable milk, they have a weakness, namely low consistency, so it is necessary to add red beans to produce a better consistency. This research was conducted to determine the right ratio of red bean sprouts to red beans to produce vegetable milk with the best characteristics. The design used in this study was a completely randomized design with a comparison of red bean sprouts and red bean sprouts, which consisted of 6 levels: 100:0, 90:10, 80:20, 70:30, 60:40, and 50:50. This research was repeated three times to obtain 18 experimental units. The data obtained was analyzed using ANOVA, and if it affected the observed parameters, it was continued with the Duncan multiple range test. The ratio of red bean sprouts to red beans had an effect on total dissolved solids, viscosity, ash content, protein, fat, color, aroma, texture, taste, and overall acceptability but had no significant effect on the pH of vegetable milk. Vegetable milk with the best treatment was obtained at a ratio of 80 percent red bean sprouts and 20 percent red beans with characteristics of total dissolved solids 12.03 Brix, viscosity 27.20 cPs, pH value 6.74, ash content 1.30 percent, protein 3, 38 percent, and 1.48 percent fat with preferred color, preferred aroma, highly preferred texture, highly preferred taste, and highly preferred overall acceptability.